(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
تعد نباتات الزينة (التلفونة) من الزراعات الاقتصادية الهامة، وقد أٌدخِلَت إلى الزراعة السورية حديثاً كإحدى أهم الزراعات البديلة، وخاصةً في الشريط الساحلي، باعتباره أحد المناطق المأمولة لانتشار هذه الزراعة.وقد تم التركيز في هذا البحث على المزايا الاقتصادية، والعوائد المادية الناتجة عن زراعة التلفونة في محافظة اللاذقية، من خلال دراسة التكاليف الانتاجية، ومؤشرات الكفاءة الاقتصادية، بالاستناد إلى بيانات ومعطيات تم جمعها من موقع البحث (عرب الملك)، معتمدين في تحديد كلفة المواد والأجور أسعار السوق السائدة في عام 2015، وقد تم السعي في هذا البحث لتحقيق الأهداف الآتية: - دراسة واقع إنتاج نباتات الزينة في سورية بشكل عام, ومحافظة اللاذقية بشكل خاص خلال الفترة 2005 - 2013. - حساب التكاليف الإنتاجية لزراعة نباتالتلفونة في محافظة اللاذقية. - إجراء التقويم الاقتصادي لزراعة نبات التلفونة في محافظة اللاذقية. وبنتيجة الدراسة تم التوصل إلى النتائج الآتية: • بلغ صافي الربح السنوي المحقق من البيت البلاستيكي الواحد من التلفونة 668212.7 ل.س. • بلغ معامل الربحية بالقياس إلى رأس المال المستثمر 27.19 %، وبالقياس إلى التكاليف الإنتاجية 49.67%. • بلغ مؤشر زمن استعادة رأس المال للتلفونة 3.67 سنة. The Ornamental Plants (Altlfona) of important economic cultivations were introduced to the recently Syrian agriculture "as one of the most important alternative cultivations, especially" in the coastal strip, as a prospective areas for the spread of these agriculture This research has concentrated on the economical properties and the profits resulting from Carnation plantation in Latakia Governorate studying the productivity cost and the indicatives of economical feasibility based on data and statements gathered from site of research(Arab Almelik),and relying, in determining wages and materials costs, on the current market prices in 2015. In this research, we havesought to achieve the following targets: - Studying the reality the production of Ornamental Plants in the Syria, in general, andLatakia Governorate, inparticular, during the period from 2005 to 2013. - Calculating the productivity cost of Altlfona plants inLatakia Governorate. - Making an economical evaluation of Altlfona plants inLatakia Governorate. In conclusion, we have reached the following result: • Totally achieved net profit per annum from one greenhouse of Altlfona plantation amounted to 668212.7Syrian Pounds. • Profitability Coefficient in proportion to invested capital has amounted to 27.19% and to 49.67% in proportion to the productivity cost. • Time indicator of Capital recovery for Altlfona has amounted to 3.67 years.